REHABILITATIONFunctional testing of muscles in patients with pectus excavatum – indications for preoperative rehabilitation - Jarosz, Maria Anna; Barinow-Wojewódzki, Aleksander; Wiernicka, Marzena; Pawlak, Krystian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
Introduction : Studies of people with pectus excavatum usually relate to physiological abnormalities caused by the deformity, as well as its impact on posture. Little is known about muscle length disorders associated with this defect. Aim of the study : Determining whether the presence of pectus excavatum is associated with changes in muscle length; developing guidelines for preoperative rehabilitation of pectus excavatum patients. Material and methods : 19 patients aged 13-19 years with diagnosed pectus excavatum were examined and qualified for the Nuss procedure at the Wielkopolska Centre of Pulmonology and Thoracosurgery in Poznań. The control group consisted of 30 healthy boys of similar age. Each patient underwent a total of 42 functional tests measuring the length of individual muscles. Results: A comparative analysis of the study and control groups in terms of muscle flexibility showed significant differences in the results of 8 tests of the 42 tests carried out (19.04%). These tests assessed the length of the pectoralis major (clavicular part, right and left), the internal rotators of both humeral joints, the iliopsoas muscle (left lower extremity) and the rectus femoris muscles (right and left), and the ischiocrural muscles (left lower extremity) – the muscles were shortened significantly more often in boys without pectus excavatum. Boys with this deformity had significantly lower body weight and a significantly lower BMI (body mass index) compared to boys in the control group. Conclusions : When planning a physiotherapy programme for pectus excavatum patients, an individualized approach should be used to achieve the best possible results.